Misklasifikasi Pasien Penyakit Jantung di Indonesia: Tinjauan Sistematis Menggunakan PRISMA: Bernadus Rudy Sunindya - Bernadus Rudy Sunindya (STIKes Persada Husada Indonesia, 2025)
Cardiovascular disease remains the leading cause of death in Indonesia, yet epidemiological and administrative data are often inaccurate due to misclassification. Misclassification can occur at the clinical level (misdiagnosis), diagnostic level (limitations in biomarkers, ECG, or imaging), and administrative level (incorrect ICD-10 coding). This article systematically reviews the evidence on forms, causes, and impacts of misclassification of heart disease patients in Indonesia using the PRISMA framework, and identifies strategies for mitigation. Literature searches were conducted in PubMed, Scopus, Google Scholar, and national portals (Ministry of Health, PERKI, Riskesdas) using keywords related to misclassification of cardiovascular disease in Indonesia. From 512 articles identified (2012–2025), 41 were fully screened, and 11 met the inclusion criteria. Data were synthesized narratively due to heterogeneity among studies. Misclassification was most frequently observed in three domains: (1) clinical—heart failure misdiagnosed as COPD, (2) diagnostic—reliance on a single biomarker without imaging verification leading to misdiagnosed acute coronary syndromes, and (3) administrative—incorrect ICD-10 coding. National surveys such as Riskesdas 2018 and SKI 2023 also highlighted discrepancies in prevalence estimates. Misclassification of heart disease in Indonesia is a multidimensional issue impacting epidemiological accuracy, clinical quality, and financing systems. Strengthening diagnostic algorithms, training ICD-10 coders, and implementing integrated digital audits are essential to reduce misclassification rates.